2021
DOI: 10.1126/science.abd9338
|View full text |Cite
|
Sign up to set email alerts
|

Inferring the effectiveness of government interventions against COVID-19

Abstract: Governments are attempting to control the COVID-19 pandemic with nonpharmaceutical interventions (NPIs). However, the effectiveness of different NPIs at reducing transmission is poorly understood. We gathered chronological data on the implementation of NPIs for several European, and other, countries between January and the end of May 2020. We estimate the effectiveness of NPIs, ranging from limiting gathering sizes, business closures, and closure of educational institutions to stay-at-home orders. To do so, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

39
978
6
21

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 915 publications
(1,044 citation statements)
references
References 67 publications
39
978
6
21
Order By: Relevance
“…Reductions of R per intervention Other papers, e.g. [12,87], report, for various interventions, corresponding percent reductions of R. Our model clarifies that it is structurally more robust to report the additive reduction of the reinfections by a certain intervention. For example, according to our model closing schools removes the school reinfections from the dynamics, and in consequence reduces R by about 0.15.…”
Section: Methods and Resultssupporting
confidence: 54%
“…Reductions of R per intervention Other papers, e.g. [12,87], report, for various interventions, corresponding percent reductions of R. Our model clarifies that it is structurally more robust to report the additive reduction of the reinfections by a certain intervention. For example, according to our model closing schools removes the school reinfections from the dynamics, and in consequence reduces R by about 0.15.…”
Section: Methods and Resultssupporting
confidence: 54%
“…The role of schools in severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection and transmission is highly debated and ranges from "there is no evidence of danger" (1) to "overlooked or at risk" (2,3). This pronounced contradiction has its roots in a puzzle that has many missing pieces.…”
Section: Introductionmentioning
confidence: 99%
“…School outbreaks have been described (2,9), but it is not clear how frequently they occur and how much they contribute to the spread of SARS-CoV-2 on a population level. Retrospective modeling studies based on many assumptions are highly controversial (1,3,10,11). Some groups have shown that closing schools and universities without making a distinction between these different settings, was associated with a 38% reduction of the reproduction factor R during the first wave of the SARS-CoV-2 pandemic (3).…”
Section: Introductionmentioning
confidence: 99%
“…To date, most data-driven policy analyses have been retrospective and focused on overall effectiveness across a number of counties, states, or countries [7][8][9][10]. These analyses can be broadly useful for policy makers deciding which controls to apply when attempting to contain an outbreak already in progress.…”
Section: Introductionmentioning
confidence: 99%